Cottonseed Press Cake as a Potential Diet for Industrially Farmed Black Soldier Fly Larvae Triggers Adaptations of Their Bacterial and Fungal Gut Microbiota - Tegtmeier, Dorothee; Hurka, Sabine; Klüber, Patrick; Brinkrolf, Karina; Heise, Philipp; Vilcinskas, Andreas (Frontiers in Microbiology, 2021)
Black soldier fly larvae (Hermetia illucens, Diptera: Stratiomyidae) are used for the bioconversion of organic side-streams into valuable compounds such as proteins, lipids and chitin. However, the economic competitiveness of farmed insects compared to conventional protein production systems in agriculture and aquaculture depends on the availability of large quantities of inexpensive insect feed. Cottonseed press cake (CPC) is a side-stream of cotton production that is rich in proteins and lipids but unsuitable as feed for several farmed animals, except ruminants, due to the presence of the anti-nutritional sesquiterpenoid gossypol. Here, we tested CPC as a feed for black soldier fly larvae and studied the impact of this diet on the gut microbiome. Larvae reared on CPC developed normally and even showed a shorter life-cycle, but were smaller at the end of larval development than control larvae reared on chicken feed. The adaptability of the larvae to different diets is mediated by their versatile gut microbiome, which facilitates digestion and detoxification. We therefore used amplicon sequencing to analyze the bacterial and fungal communities associated with larvae reared on each diet, revealing differences between the larval guts and frass (residual feed substrate) as well as differences between the two diet groups. For example, Actinomycetaceae and Aspergillaceae were significantly enriched in guts of the CPC diet group and may help to metabolize compounds such as gossypol. Potentially probiotic yeasts and beneficial Enterobacteriaceae, which presumably belong to the core microbiota, were detected in high relative abundance in the gut and frass, indicating a functional role of these microbes, especially the protection against pathogens. We conclude that CPC may be suitable as an inexpensive and environmentally sustainable feed for the industrial rearing of black soldier flies.